Application of immunotherapy for neurological manifestations in hypermobile Ehlers–Danlos syndrome. (August 2018) - Araki, Manabu; Lin, Youwei; Ono, Hirohiko; Sato, Wakiro; Yamamura, Takashi
Ehlers–Danlos syndrome (EDS) is a heterogeneous heritable connective tissue disorder with various neurological manifestations, including chronic pain. The neurological manifestations in EDS are often regarded as being caused by the associated musculoskeletal disorders or polyneuropathy. Here, we present two patients with hypermobile EDS (hEDS), presenting with relapsing central nervous system (CNS) manifestations. Although the two patients showed relapsing signs of CNS manifestations like multiple sclerosis (MS) or neuromyelitis optica spectrum disorder (NMOSD), they were unique in that they had widespread opioid-dependent chronic pain, which is not consistent with the symptoms of MS/NMOSD. Unexpectedly, the serious pain of unknown origin was remarkably mitigated by plasmapheresis, and magnetic resonance imaging (MRI) examinations conducted for one of the patients were negative. Collectively, we speculate that hEDS may be more susceptible to 'normal-appearing imaging, neuroimmunologically justified, autoimmune-mediated encephalomyelitis (NINJA).' Analysis of the presented cases and an additional three patients with EDS with chronic pain indicates that treatable immune-mediated mechanisms deserve considerations for neurological symptoms observed in hEDS.